KEMAMPUAN MEMBACA AL-QUR’AN SISWA SD ISLAM KHAIRA UMMAH PADANG - Efendi Efendi; Mediawati Melayu (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
This study aims to (1) To know the ability of reading al-Qur'an Khaira Ummah Islamic Elementary School students Padang. (2) PAI teacher business in improving students' Quran Reading Ability of Class IV and V at Khaira Ummah Islamic Elementary School in Padang. This research is field research (field research), This research type is qualitative research with descriptive approach. Primary data sources in this study were PAI teachers and classroom teachers, while the secondary data sources were principals, students, and school documents. data collection techniques that the author uses are oral tests, observation, interviews and documentation. To analyze the data the authors use descriptive qualitative analysis, which describes the problems that occur in the field as is. Step analysis of data is data reduction, data presentation, conclusion. Based on the research that has been done by the writer in Islamic Elementary School of Khaira Ummah Padang can be known (1) Ability of students to read al-Qur'an from 104 students found 77 get value between 84 until 91, the value belong to good category, 25 students get value between 74 and 79, this value belongs to a simple category, and 2 students gain a score of between 40 to 59, this value belongs to the weak category (2) Teachers improve skills by giving motivation to learn, be good, create atmosphere in learning , varied teaching methods, reading habits of the Qur'an and giving training tasks in accordance with the ability of learners